The Barriers of Sharing the Supply Chain Knowledge and Methods of Treatment: Case Study in a Sample of the Faculties of the University of Mosul - Ali Abdul Sattr Abdul Jabbar Al-Hafidh (International Journal of Supply Chain Management, 2018)
This study aimed to examine the barriers surrounding sharing the supply chain knowledge and the successful ways to minimize the barriers of sharing the supply chain knowledge. The study also set to investigate different ways to reduce the negative impacts of knowledge sharing in the faculties of the University of Mosul. The study adopted questionnaires designed from a group of article journals and the respondents were selected from the faculties in the University of Mosul. A set of conclusions were developed after identifying the challenges of sharing the supply chain knowledge using statistical methods to analyse the data from the faculties of Mosul University. From the conclusion, the study recommended the need to give employees more confidence and the advantage of motivation in reducing barriers to knowledge sharing in the university.